2018
DOI: 10.1159/000495871
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA SNHG8 Promotes the Tumorigenesis and Metastasis by Sponging miR-149-5p and Predicts Tumor Recurrence in Hepatocellular Carcinoma

Abstract: Background/Aims: Long noncoding RNAs (lncRNAs) are aberrantly expressed in multiple malignant tumors involved in tumor growth and metastasis. Accumulating data show that small nucleolar RNA host gene (SNHG) 1/12/20 plays a key role in the progression of hepatocellular carcinoma (HCC). However, the molecular mechanisms by which SNHG8 contributes to HCC remain elusive and merit exploration. Methods: The association between SNHG8 expression and the clinicopathological characteristics and prognoses in HCC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 30 publications
7
66
0
Order By: Relevance
“…Recently, many studies have found that the aberrant expression of snoRNAs might act as an oncogene in the progression of the tumor. For example, Chen found that SNHG8 overexpressed in non-small cell lung carcinoma (NSCLC) [32], and Dong found that SNHG8 is an oncogene in human hepatocellular carcinoma [33], Meng found SNHG6 promotes glioma tumorigenesis in glioma [34], and Zhu found SNHG4 overexpressed in hepatocellular carcinoma [35]. Consistent with these studies, we found higher SNHG4 expression in liver cancer and it may be a biomarker.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, many studies have found that the aberrant expression of snoRNAs might act as an oncogene in the progression of the tumor. For example, Chen found that SNHG8 overexpressed in non-small cell lung carcinoma (NSCLC) [32], and Dong found that SNHG8 is an oncogene in human hepatocellular carcinoma [33], Meng found SNHG6 promotes glioma tumorigenesis in glioma [34], and Zhu found SNHG4 overexpressed in hepatocellular carcinoma [35]. Consistent with these studies, we found higher SNHG4 expression in liver cancer and it may be a biomarker.…”
Section: Discussionsupporting
confidence: 86%
“…1A). The carcinogenesis function of SNHG family in cancers has been widely reported (Cai et al, 2017;Dong et al, 2018), and the participation of SNHG1 and SNHG7 in ESCC has been researched (Xu et al, 2018a;Zhang et al, 2017), so we focused on SNHG12 in our research. Then, qRT-PCR data depicted that SNHG12 was higher in ESCC tissues than paired para-tumor specimens ( Fig.…”
Section: Snhg12 Expression Is Upregulated In Escc Tissues and Cellsmentioning
confidence: 99%
“…Cell biofunction experiments verified that SNHG7 could increase cell invasion ability, which implied that SNHG7 acted as an oncogene to promote tumorigenesis. Dong et al regarded that SNHG8 promoted liver cancer tumorigenesis and pulmonary metastasis via sponging MIR149 . SNHG12 was the host gene of four small nucleolar RNAs— SNORA44 , SNORA61 , SNORA16A and SNORD99 .…”
Section: Biological Functions and Mechanisms Of Snhgs In Digestive Camentioning
confidence: 99%